MENINGKATKAN MOTIVASI DAN KETERAMPILAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL MAHIR PADA SISWA SEKOLAH DASAR - ulm, Nadia mhs; Sari, Dessy Dwitalia (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
The problem encountered in this study is low motivation and critical thinking skills in Civic learning. This study aims to find solutions to problems that arise when students do not think critically or are not motivated to learn. This research examines the learning outcomes, motivation and critical thinking of students to reflect the growth of learning quality. This Classroom Action Study (PTK) was conducted in four meetings. The subjects of the study were 12 fifth grade students at SDN Pekauman 2 Banjarmasin of which 4 were female and 8 were male. Qualitative data is taken through observation of learning motivation and critical thinking, while quantitative data is taken from student learning results obtained through individual and group written tests. Measurement of learning success if 80% of students must meet or exceed KKM ie ≥70. Based on the results of the study and findings, it was concluded that teaching and learning process activities using the MAHIR learning model (Problem Based Learning, Numbered Head Together, Picture and Picture) can increase learning motivation and critical thinking skills. from elementary school students.